Attending to the chemical senses - Spence, C (Brill Academic Publishers, 2019)
Theorizing around the topic of attention and its role in human information processing largely emerged out of research on the so-called spatial senses: vision, audition, and to a lesser extent, touch. Thus far, the chemical senses have received far less research interest (or should that be attention) from those experimental psychologists and cognitive neuroscientists interested in the topic. Nevertheless, this review highlights the key role that attentional selection also plays in chemosensory information processing and awareness. Indeed, many of the same theoretical approaches/experimental paradigms that were originally developed in the context of the spatial senses, can be (and in some cases already have been) extended to provide a useful framework for thinking about the perception of taste/flavour. Furthermore, a number of those creative individuals interested in modifying the perception of taste/flavour by manipulating product-extrinsic cues (such as, for example, music in the case of sonic seasoning) are increasingly looking to attentional accounts in order to help explain the empirical phenomena that they are starting to uncover. However, separate from its role in explaining sonic seasoning, gaining a better understanding of the role of attentional distraction in modulating our eating/drinking behaviours really ought to be a topic of growing societal concern. This is because distracted diners (e.g., those who eat while watching TV, fiddling with a mobile device or smartphone, or even while driving) consume significantly more than those who mindfully pay attention to the sensations associated with eating and drinking.